Flood Prevention and Mitigation Initiatives towards a Flood-Free City - S.Subia, Engr. Gener; C. Jocson , Engr. Joefil; T.Florencondia , Engr. Noel (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
This study aimed to investigate the flood prevention and mitigation initiatives of Cabanatuan to gain information that served as the basis for the development and integration of flood prevention and mitigation initiatives in the City. The researcher used the descriptive research design with questionnaire as the main tool to gather information from the 110 barangay residents and officials, Local Government Units (LGU) and Cabanatuan City Disaster Risk Reduction and Management Office officers (CCDRRMO) of the City. The study found out that: a. Cabanatuan City is vulnerable to floodings; barangays in Cabanatuan that are more flood physical vulnerable are Aduas Centro, Aduas Norte, Aduas Sur, Bagong Sikat, Bakero, Bakod Bayan, Bantug Bulalo, Barlis, Barrera and Balite; b. Heavy and prolonged rainfall, clogged river, canals, creeks and streams, lack of preventive infrastructure and facilities and poor implementation of waste management system were the possible leading causes of flooding in Cabanatuan City; c. The flood prevention and mitigation initiatives as to control over the river and control over the land were moderately implemented while other mitigation measures that had been done by the City Government were properly implemented; d. There is no significant difference in the responses of the three groups of respondents regarding the flood prevention and mitigation initiatives done by the Cabanatuan City government; e. Monthly seminars regarding floods for proper awareness and readiness, strict implementation of the law, appropriate coordination with community and government authorities and better flood prevention and mitigation plan were the suggestions of the respondents towards a flood-free city.